Concurrent B Cell Acute Lymphoblastic Lymphoma/Leukemia and Monoclonal B Cell Lymphocytosis: A Case Report with Extensive Molecular Analysis - Mehdipour Dalivand, Maryam; Tizro, Parastou; Partain, Julie; Aggarwal, Anita; Lichy, Jack; Mot Ara, Francisco; Nava, Victor E. (Case Reports in Hematology, 2022)
Although acute lymphoblastic leukemia (ALL) and monoclonal B cell lymphocytosis (MBL) are common neoplasia, a simultaneous presentation is very unusual. Here, we present two different B cell clones, MBL and B-ALL, cocirculating in a 78-year-old African American male. Detailed molecular characterization revealed an unusual MPL (T487I) point mutation and unmutated VH4-39. After nonstandard chemotherapy, the patient remains in morphologic remission. These findings may stimulate further research to clarify the pathogenesis of hematologic neoplasms.